THE ROLE OF POLITENESS IN APOLOGY SEQUENCES: HOW TO MAINTAIN HARMONY BETWEEN SPEAKERS - Martínez-Flor, Alicia; Beltrán-Palanques, Vicente (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract The goal of the present paper is to provide a discourse-based teaching approach for the integration of the speech act of apologies from a communicative perspective. In so doing, special attention is paid to how sociocultural norms affect language use. The rationale behind the selection of this speech act is based on the fact that the realisation of this pragmatic aspect might be complex for learners of English as a Second/Foreign Language (SL/FL) not only when selecting appropriate utterances, but also in assessing what an offense involves and its severity (Bergman and Kasper, 1993). Taking these aspects into account, this paper provides first a review of politeness theory, then, a description of the speech act under investigation is presented, and finally, pedagogical implications regarding the integration of apologies in the second/foreign language classroom are suggested. Resumen El objetivo de este trabajo es presentar un enfoque instructivo desde una perspectiva discursiva para la integración del acto de habla de la disculpa desde una perspectiva comunicativa. De este modo, se da especial atención a cómo las normas socioculturales afectan al uso del lenguaje. Se ha seleccionado este acto de habla puesto que su realización podría ser compleja para los estudiantes de inglés como segunda lengua/lengua extranjera (SL/LE) no sólo en la selección de estrategias apropiadas, sino también en cuanto a la evaluación de lo que una ofensa implica y cuál es su severidad (Bergman y Kasper, 1993). Teniendo en cuenta los aspectos mencionados, este trabajo presenta en primer lugar una revisión de la teoría de la cortesía, en segundo lugar, una descripción del acto de habla objeto de estudio, y finalmente se proponen sugerencias pedagógicas respecto a la integración de disculpas en el aula de segundas lenguas/lenguas extranjeras.